Two Generalized Predator-Prey Models for Integrated Pest Management with Stage Structure and Disease in the Prey Population - Ruiqing Shi; Sanyi Tang; Wenli Feng (Abstract and Applied Analysis)
Stage-structured predator-prey models with disease in the prey are constructed. For the purpose of integrated pest management, two types of impulsive control strategies (impulsive release of infective prey and impulsive release of predator) are used. For Case  1, infective prey applications are more frequent than releases of predator (natural enemies). For Case  2, predator (natural enemies) releases are more frequent than infective prey applications. In both cases, we get the sufficient conditions for the global attractivity of the susceptible prey-eradication periodic solution. In addition, the persistence of the systems is also discussed. At last, the results are discussed and some possible future work is put forward.